Before Objectivity: The Concept of Distributive Knowledge in Early Modern Metaphysics - Malyshkin, Eugeny; Shipovalova, Lada (Problemos, 2016)
The paper discusses the concept of distribution of ideas and, accordingly, of knowledge, which can be found in the early modern metaphysics. This concept was not completely developed and was overshadowed by the concept of objectivity. An attempt to formalize the distributivity is made. The role played by the idea of distributive knowledge in pre-Kantian metaphysics is demonstrated with a special attention to Leibniz’s doctrine. We argue, that the events of communication between individuals are based on points of distributive knowledge.